G. M. Hopkins’ God’s Grandeur: An Aesthetic Delight (Patan Prospective Journal, 2024)
This research paper intellectually sheds light on aesthetic delight in Gerard Manley Hopkins' God's Grandeur. This study based on qualitative research approach examines how God’s grandeur generates the aesthetic delight or beauty to uphold the intellectual knowledge. The purpose or the objective of the research paper is to make an analysis examination of God’s greatness. The poet's firm belief in the glory of God/Nature proves to be an inspiring approach/method to enlighten readers on his sonnet God's Grandeur. This poem, God's Grandeur, appeals to the intellectual mind, manner and moral. This genre in literature depicts the creation and nature of the incorporeal world. The creator of the universe plays an inspirational role to acknowledge the God's glory and beauties in the world. The role of the Creator/God is spelt out in the title of the poem i.e. God's Grandeur. The message that the poem imparts is significant: what is corporeal and incorporeal becomes clear only after it appeals to the intellectual mind. The study helps us to elevate God's Grandeur. It adopts an analytical research design. Hopkins, a Nature poet, is well aware of God's gifts and beauties. How Hopkins’ poem explains the glory of God is the statement of the study. The facts and figures of divine grandeur contribute to the readers' positive response to the poem. The use of intellectual insight transcends the unseen and incorporeal forms. So, the importance of intellectual mind is highlighted by the aesthetic delight that the poem generates for both secular and religious societies. People in the world, however, are less spiritual and more physically and materially conscious.